1273 Investigating prescribing errors in salbutamol nebulisers for acute asthma patients aged 5 and above in a district general hospital. (17th August 2022) - Moody, Michael; Williams, Gemma
Abstract : Aims: Prescribing and managing acute Paediatric presentations in A&E varies on experience and confidence of clinicians, availability of trained nursing staff and using correct guidelines. Coupled with recent pressures from Covid-19, this can increase prescribing errors and incorrect management of patients. This audit investigated prescribing errors against the Trust's latest Acute Asthma guidelines for patients aged five and above in Scarborough Hospital's A&E department to determine levels of safe and correct prescribing in severe/life threatening asthma. Methods: Data was interrogated from A&E admissions between 1 st September to 31 st December 2021, for patients treated for Severe/Life Threatening Asthma, or allergic reactions needing nebulisers. Patients with viral wheeze, no nebuliser prescriptions on admission (CAS) cards, and presenting to A&E as mild/moderate asthma but were severe/life-threatening in ambulance were excluded. 47 patients were produced, and 21 were used after matching the Trust's Acute Asthma guideline (figure.1) [1]. Results: Findings show almost every patient requiring nebulisers received them; however there were fewer than expected patients receiving correctly prescribed nebulisers that met the guidelines ( figure 2 ). This appeared to be due to smaller than required nebuliser doses or being transferred when they required a further set of nebulisers. Further analysis identified when a Paediatric ED nurse was on shift there were substantially more correct prescriptions ( figure 2 ). This indicates the importance of having Paediatric trained nurses in A&E departments to help cross-check prescriptions. The 19% of patients where Paediatric ED nurses were present who had incorrect prescriptions was from smaller prescribed doses of nebulisers than required. Investigating prescribing errors and clinician grade highlighted there were more common errors among Registrar doctors, and fewer among Foundation Doctors, ACCS and GP trainees ( figure 3 ). These again account for smaller nebuliser doses being prescribed for five year old patients, possibly from following the 2019 guidelines stating 2.5mg Salbutamol nebulisers were for two to five year olds [2]. Finally some patients failing the guidelines highlighted concerns, mainly in the delay of giving nebulisers in an adequate timeframe. These included initial nebulisers being prescribed but no follow up nebulisers being given quick enough. Conclusion: This Audit shows the importance of having confident and experienced Paediatric trained clinicians in A&E, as well as showing that the presence of Paediatric ED nurses improves safe prescribing. It also highlights difficulties in keeping up-to-date with latest guidelines as registrar grades showed more deviation away from current guidelines than junior staff, showing their reliance on previous experience. Follow up will include auditing the department while incorporating a modern prototype laminated flipbook for acute/emergency Paediatric presentations following standardised WETFLAG numbers, conditions, and management requirements all by age and cross checked by Paediatric ED nurses to improve confidence and prescribing in A&E staff as well as teaching sessions for new starters to the department highlighting where to find departmental guidelines. [1] Protocol for the Management of Acute Asthma in Children 5 years and over, Authors Felicity Dick, Paediatric ED Sister & Jen Brownbridge, Paediatric Respiratory Nurse [2] SIGN158: British guideline on the management of asthma. Scottish Intercollegiate Guidelines Network, 2019.